Pluripotential Theory Cetraro, Italy 2011, Editors: Filippo Bracci, John Erik Fornæss - Patrizio, Giorgio; Błocki, Zbigniew; Berteloot, Francois; Demailly, Jean Pierre (C.I.M.E. Foundation Subseries, 2013)
Pluripotential theory is a very powerful tool in geometry, complex analysis and dynamics. This volume brings together the lectures held at the 2011 CIME session on "pluripotential theory" in Cetraro, Italy. This CIME course focused on complex Monge-Ampére equations, applications of pluripotential theory to Kahler geometry and algebraic geometry and to holomorphic dynamics. The contributions provide an extensive description of the theory and its very recent developments, starting from basic introductory materials and concluding with open questions in current research.